2017
DOI: 10.1167/iovs.16-20913
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Therapy for Childhood Amblyopia Improves Vision Without Breaking Interocular Suppression

Abstract: BBV is a binocular treatment for amblyopia that can be self-administered at home (with remote monitoring), producing rapid and substantial benefits that cannot be solely mediated by a reduction in interocular suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 81 publications
1
93
0
Order By: Relevance
“…Classical patching therapy might be counterproductive for the development of coordinated vergence eye movements because it forces the two eyes to work independently and does not favor the correct development of binocular oculomotor control. Dichoptic therapies that attempt to balance the input to the two eyes and favor conjugate eye movements might be better suited to ensure binocular cooperation [36,93,44,52,89,90,56,9]. Here, we have shown that the link between the oculomotor and hand motor system is unaffected by simulated visual impairment.…”
Section: Clinical Significance Of Our Findingsmentioning
confidence: 72%
“…Classical patching therapy might be counterproductive for the development of coordinated vergence eye movements because it forces the two eyes to work independently and does not favor the correct development of binocular oculomotor control. Dichoptic therapies that attempt to balance the input to the two eyes and favor conjugate eye movements might be better suited to ensure binocular cooperation [36,93,44,52,89,90,56,9]. Here, we have shown that the link between the oculomotor and hand motor system is unaffected by simulated visual impairment.…”
Section: Clinical Significance Of Our Findingsmentioning
confidence: 72%
“…In the level III study by Vedamurthy et al 16 that used a combination of perceptual learning and dichoptic therapy, stereoacuity improved by a mean of 0.18 log arc seconds (SD, 0.05 log arc seconds) in the active game group and 0.08 log arc seconds (SD, 0.04 log arc seconds) for the monocular movie-viewing group (P < 0.005). In the 2017 level III study of BBV reported by Bossi et al, 33 the number of children with measurable stereoacuity increased from 1 of 7 of the anisometropic amblyopes pretreatment to 6 of 7 posttreatment. In these 7 subjects, the median stereoacuity improved from 170 arc seconds (interquartile 230 arc seconds) to 85 arc seconds (interquartile 30 arc seconds) (P ¼ 0.0215).…”
Section: Binocularity and Sensory Outcomes Such As Stereopsismentioning
confidence: 91%
“…Bossi et al 33 reported another form of dichoptic therapy in 2017 that they described as balanced binocular viewing (BBV) treatment. This therapy uses a computer and shutter glasses to present dichoptic movies that are matched in visibility across the eyes.…”
Section: Amblyopic Eye Visual Acuitymentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical relevance of the dominant eye is now well-accepted, as several studies have since verified the existence of physiological, sensory and motor bases for ocular dominance in patients with normal binocularity and equal refractive errors [10][11][12][13][14][15][16][17][18]. For example, Hofeldt concluded that placing a moderate neutral density filter over the dominant eye diminished motion task performance more than placing the filter over the non-dominant or both eyes [12].…”
Section: Introductionmentioning
confidence: 99%